IMPLEMENTATION OF INFORMATION SYSTEM APPLICATION POLICY TO IMPROVE THE QUALITY OF RECORDING INVENTORY GOODS AT THE CLASS I TPI CIREBON IMMIGRATION OFFICE - Alamsyah, Riza; Sutrisno, Endang; Hidayat, Moh. Taufik (Journal of Social and Economics Research, 2025)
This study aims to identify, explore, and analyze the factors that influence the implementation of an inventory information system application in improving the quality of inventory records at the Class I Immigration Office TPI Cirebon. The implementation of this application is expected to contribute to the realization of good governance through more efficient, accurate, and transparent service and administrative management. This research uses a descriptive qualitative approach with a phenomenological method. Data collection techniques include observation, in-depth interviews, document analysis, and archival research. The informants consist of office leaders, application operators, civil servants, and community service users. Data analysis is carried out through data reduction, data presentation, and conclusion drawing. The results show that the implementation of the inventory information system application has been carried out in both internal and external services. However, it has not yet been optimal due to several challenges, such as limited access via Android devices, the unavailability of integrated service features for inventory recording, and inadequate internet bandwidth. This research provides strategic recommendations for system development to become more adaptive, efficient, and responsive to user needs.